1998
DOI: 10.1023/a:1008950902047
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction by calcium phosphate biomaterials

Abstract: Different materials were implanted in muscles of dogs to study the osteoinduction of calcium phosphate biomaterials. Bone formation was only seen in calcium phosphate biomaterials with micropores, and could be found in hydroxyapatite (HA) ceramic, tricalcium phosphate/hydroxyapatite ceramic (BCP), beta-TCP ceramic and calcium phosphate cement. The osteoinductive potential was different in different materials. The results indicate that osteoinduction can be a property of calcium phosphate biomaterials when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
288
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(302 citation statements)
references
References 8 publications
10
288
1
3
Order By: Relevance
“…Since then, generous attention was paid to these kinds of biomaterials, such as synthetic hydroxyapatite ceramics (HA), porous biphasic calcium phosphate ceramics (BCP), tricalcium phosphate ceramics (TCP), calcium pyrophosphate ceramics, and coralderived hydroxyapatite. These ceramic materials have been shown to have intrinsic osteoinduction (Ducheyne and Cuckler, 1992;Toth et al, 1993;Yang et al, 1997;Yuan et al, 1998a;1998b;Nihouannen et al, 2005;Ye et al, 2007;Fellah et al, 2008). However, the main evidence of bone formation in these biomaterials was based on histological analysis and there were few reports focusing on the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, generous attention was paid to these kinds of biomaterials, such as synthetic hydroxyapatite ceramics (HA), porous biphasic calcium phosphate ceramics (BCP), tricalcium phosphate ceramics (TCP), calcium pyrophosphate ceramics, and coralderived hydroxyapatite. These ceramic materials have been shown to have intrinsic osteoinduction (Ducheyne and Cuckler, 1992;Toth et al, 1993;Yang et al, 1997;Yuan et al, 1998a;1998b;Nihouannen et al, 2005;Ye et al, 2007;Fellah et al, 2008). However, the main evidence of bone formation in these biomaterials was based on histological analysis and there were few reports focusing on the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The ceramic may also potentiate the activity of BMPs by binding the protein and presenting it to target cells. Former studies have already described an upregulation of BMPs by CaP bone grafts [97]. BMP-2 has been detected immunohistochemically in the host region around the grafted particles during early healing of a nanostructured sHA [60], indicating an absorption of these factors or activating endogenous BMP from the environment.…”
Section: Osteoconduction or Osteoinduction?mentioning
confidence: 94%
“…In general, the nanoporosity in scaffolds could significantly promote osteoinductivity during bone tissue engineering by enhancing osteogenic differentiation [13,14], as many natural tissues like bone can be regarded as materials with some nanostructures. It was also found that both macro and micro porosity could influence osteoinductive activity to certain extent [10,11]. Particularly, the microporosity in the scaffolds is able to make substantial contribution to bone regeneration [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…Owing to its similarity to the natural bones in chemical composition, HA (hydroxyapatite, Ca 10 [PO 4 ] 6 [OH] 2 ) has become an excellent biomaterial as substitutes of natural bones [3][4][5][6]. However, the uses of HA for bone regenesis have encountered a number of technical challenges, including its resistance to biodegradation in vivo [5], low fracture toughness, and high crystallinity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation